Delay in the Distribution of Productive Inheritance Assets: A Sharia-Based Analysis Through the Methodology of Taha Jabir Al-Alwani - Tri Hasan Bashori; Asmuni (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze the validity of the postponement of inheritance distribution in productive assets using the perspective of maqāṣid al-syari'ah Taha Jabir al-Alwani. The focus is to balance the provisions of inherited fiqh with the need to maintain the family's economic sustainability. Theoretical framework: The research uses the contemporary maqāṣid al-shari'ah theory of Taha Jabir al-Alwani, which consists of three main pillars: al-Tauhid, al-Tazkiyah, and al-'Umran. These three pillars are the basis for assessing the benefits of postponing the distribution of inheritance. Literature review: A literature review discusses the differences between the classical fiqh of inheritance that encourages immediate division and the contemporary maqāṣid approach that takes into account modern socio-economic conditions. The literature also covers the concept of productive asset management in Islam. Method: The research uses normative qualitative methods with a conceptual and maqāṣid approach. The analysis was carried out through the method of al-jam'u bayna al-qirā'atain, which is to connect sharia texts with social reality. Results: The results of the study show that the postponement of inheritance distribution can be allowed if it meets the principles of justice (al-Tauhid), transparency and agreement (al-Tazkiyah), and is able to increase the economic benefits of assets (al-'Umran). If it causes conflict or loss, then the practice is not justified. Implications: This study provides guidelines for judges, mediators, and families in resolving disputes over the inheritance of productive assets. The results can be used as a basis for more benefit-oriented decision-making. Novelty: The novelty of the research lies in the use of maqāṣid al-shari'ah Taha Jabir al-Alwani to assess the delay in the distribution of inheritance of productive assets. This research expands the concept of ḥifẓ al-māl from simply maintaining wealth to productive and sustainable wealth management.